Cross-Cultural Comparison of the Espresso Protocol Repeatability - Jisoo Choi; Jeehyun Lee; Edgar Chambers (Foods)
The Espresso Protocol (TEP) was used to assess the quality of coffee beans through espresso extraction incorporating a sensory approach. TEP includes overall quality evaluation and attribute evaluation using check-all-that-apply (CATA). This study aims to evaluate the repeatability of TEP when used by experts and to compare cross-cultural assessments to determine its applicability across different countries with diverse coffee cultures. Experts with over three years of experience in the coffee industry from five countries—France (n = 7), India (n = 12), Italy (n = 7), the Republic of Korea (n = 10), and the USA (n = 10)—participated in our study. The experiment was conducted in three replications using eight different single-origin coffee samples over two or three consecutive days. Cluster analysis using CATA data was performed to verify the repeatability of individual participants in the characterization of espresso samples, revealing that most participants were repeatable in their three-time evaluations. Moreover, a significant homogeneity index demonstrated a high degree of similarity in the sensory characteristics used by experts from each country, although cultural differences were observed in the terminology used to describe coffee. In conclusion, the repeatability of individual experts and the reliability of TEP were successfully demonstrated. However, some differences in sensory evaluations were noted across cultures; these were likely influenced by differences in the use of terminology, which emphasizes the need for training in the coffee lexicon.